RESTITUTION, COMPENSATION OR INVESTMENT? – THE REPRIVATIZATION OF THE GERMAN DEMOCRATIC REPUBLIC ASSETS - Falkowska, Anna (Ekonomia i Prawo. Economics and Law, 2011)
The article illustrates a process of property`s restitution within the boundaries of the former GDR. It presents the initial arrangements in this regard between the two German states, concluded in Joint Declaration and Unification Treaty, which provided an obligation to return assets expropriated by the state to its rightful owners or their heirs. This principle of restitution was subsequently developed in the Property Law of 1990. In order to stimulate investment further legislation, however, introduced exceptions to this rule, giving finally priority to investors over former owners rights. The aim of this article is to draw a conclusion from German experiences and to find clues for the regulation of still unresolved restitution issues in Poland.